Clinical and Epidemiological Features of Patients with Drug-Induced Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis in Iran: Different Points of Children from Adults - Bahareh Abtahi-Naeini; Mohammad-sadegh Dehghan; Fatemeh Paknazar; Zabihollah Shahmoradi; Gita Faghihi; Ali Mohammad Sabzghabaee; Mojtaba Akbari; Mahdi Hadian; Tooba Momen (International Journal of Pediatrics)
Background. Different epidemiologic aspects of drug-induced Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) in children are scarce. Aim. To compare the clinical and epidemiological features of patients with drug-induced SJS and TEN in children and adults. Method. This retrospective study was conducted at two academic referral centers (Isfahan, Iran) over 5 years. SJS and TEN were clinically diagnosed and confirmed by skin biopsy as needed. Results. One hundred one patients (31 children and 70 adults) with a female to male ratio of 1.1 : 1 was identified in the present study. SJS was more commonly diagnosed in both pediatric and adult patients. The most frequent reason for drug administration identified was the infection (45.2%) and seizure (45.2%) in children and infection (34.3%) and psychiatry disorder (27.1%) in adults (P=0.001). The most common culprit drugs in the pediatric were phenobarbital (9/31), cotrimoxazole (4/31), and amoxicillin (4/31); however, in the adult group, the most common drugs were carbamazepine (11/70) and lamotrigine (9/70). Fever was significantly more common in adults (44.3%) compared to pediatric patients (22.6%) (P=0.03). Multiple logistic regression models showed that pediatric patients had significantly lower odds of hospitalization (OR [odds ratio]: 0.14; 95% CI 0.02, 0.67). In addition, patients with SCORTEN 1 had significantly higher odds of hospitalization (OR: 6.3; 95% CI: 1.68, 23.79) compared to patients with SCORTEN 0. Conclusions. The present study showed several differences between the pediatric and adult patients with SJS and TEN, including the reason for drug administration, culprit drugs, length of hospital stay, presence of fever, and final diagnosis of disease.